New Investigation of Millimeter-Wave Rotational Spectrum of CF3CN in the Excited Vibrational States v7=1 and v8=1 - Masoud Motamedi; Bahram Vahabzadeh Zargari (E-Journal of Chemistry)
The millimeter-wave rotational spectra of the excited vibrational states v7=1 and v8=1 of the symmetric top molecule trifluoroacetonitrile, CF3CN, have been analyzed again. The ζ=±1 series have been assigned and the rotational parameters including B7 =2944.9748(14) MHz, q+t=1.4505(16) MHz for v7=1 and B8 =2950.4853(4) MHz, q+t= 3.6035(20) MHz for v8=1states were determined accurately.